Kualitas diet dan kontrol glikemik pada orang dewasa dengan diabetes melitus tipe dua - Dodik Briawan; Mahfuzhoh Fadillah Heryanda; Sudikno Sudikno (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Diet quality and glycemic control in adults with type two diabetes mellitusBackground: As assessed by Alternate Healthy Eating Index (AHEI), diet quality is correlated with glycemic control through its effect on glucose-insulin homeostasis. Studies are evaluating the diet quality index in Indonesia, especially its relation to glycemic control in those with type 2 diabetes mellitus (T2DM), are lacking. Objective: To analyze the association between diet quality and glycemic control T2DM in adults. Methods: This research was a cross-sectional study using data from